The Extraordinary Drought of 2011/2012 in Iraq and its Possible Linkage to Large-Scale Atmospheric Circulation - Al-Sabhany, Khamis Dahahm Muslih (Al-Adab Journal, 2022)
This paper aims to analysis the drought of 2021-2022 over Iraq according to its historical context, and then tries to examining its possible connection with associated synoptic pressure patterns and the North Atlantic Oscillation (NAO). The Standard Precipitation Index (SPI) was used to exam drought severity and Mann-Kendall test used in order to compute drought trends. Three sets of data were used to achieve paper’s goal; related to annual participation from ten climatic stations in Iraq, NAO data for winter months (Dec, Jan, Feb and Mar) , and the NCEP-NCAR Reanalysis Data. The result shows the 2021-2022 was exceptional in terms of the drought severity thought the climatic record periods, with percentage of dry years more than 60%. The most extreme droughts had happened during the last 22 years with more than 80% of them in the Baghdad station as drought years. The annual drought trends analysis revealed that there are general negative trends with the strongest trends identified in the Mosul station about -0.1205 per decade. It was also found that the sustainability of the tropical flow in the upper atmosphere level, represented by a deep ridge and retreat of the polar jet stream towards north, accompanied by a location far to the north of the polar front, was the main reason for severe drought occurrence during this year. These amplified synoptic patterns were a highly persistent as a result of the sustainability of the positive phase of the North Atlantic Oscillation.